Gender Portrayal in School Textbooks: A Study in Bhopal City - Singh, Pooja; Bammi, Ruchika (Prabandhan: Indian Journal of Management, 2013)
Education is recognized as one of the critical elements for national development efforts as it is a powerful tool to build a knowledge-based society for the 21st century. The awareness and commitment for attaining gender equality can be realized as being one of the most important development goals of India. Statistics indicate that the scenario of gender equality in education has made progress by leaps and bounds; however, a camouflaged form of gender inequality in the curriculum has gone unaccounted for. The current paper documents the extent of gender inequality in the curriculum and in the textbooks adopted by the schools in Bhopal. The study is limited to analyzing the curriculum/ textbooks of Hindi and English languages for Classes I - X through content analysis. The paper also makes an effort to understand the opinion of various stakeholders regarding the curriculum being "Gender Neutral" or "Gender Sensitive". The research will add value towards building literature related to the extent of gender differences in the curriculum. The study can provide the policymakers with relevant information to build a gender-neutral curriculum for schools so as to improve access to education along with equity and excellence in education. The study will provide literature for adoption of strategies for enhancing the relevance of education through curriculum reforms.